Excimer laser in management of underexpansion of a newly deployed coronary stent. Issue 1 (1st July 2013) - Lam, Simon Cheung Chi; Bertog, Stefan; Sievert, Horst
<x xml:space="preserve">Abstract</x> We report the successful management of underexpansion of a newly deployed coronary stent refractory to balloon dilatations. Direct stenting was performed for a lesion in the mid left anterior descending artery (without angiographically apparent heavy coronary calcification). The stent remained underexpanded despite repeated balloon dilatations including with high‐pressure inflations. Subsequently, an excimer laser catheter was used in an attempt to vaporize the plaque by the accoustomechanical effect of the rapidly exploding bubbles. The overall angiographic result was good after further balloon dilatation with ordinary pressure and full stent expansion was achieved. Management of underexpansion of a newly deployed stent is a potential indication of laser angioplasty. © 2013 Wiley Periodicals, Inc.